Analisis Tingkat Kepekaan Penyerapan Tenaga Kerja Menurut Status Pekerjaan Utama di Kota Kupang 2011-2020 - Frits O. Fanggidae (Jurnal Inovasi Kebijakan, 2021)
Based on the results of the analysis and comparison, it can be concluded that employment based on main employment status in job categories 1-3 are sensitive to a decline in economic growth and employment categories 4-6 are not sensitive to a decline in economic growth. In this type of work (category 4-6), the number of workers absorbed is inversely proportional to the decline in economic growth. However, the absorption of labor in the main job status categories 4-6 which are not sensitive to the decline in economic growth, is actually a solution in the short term. In the medium and long term, the category of employment in the main job status categories 1-3 is very important as an economic foundation that supports sustainable economic growth. Therefore, in conditions of economic contraction, the government needs to provide assistance with easy access to business financing, tax incentives and relaxation of loans to financial institutions.